2018
DOI: 10.3389/fnins.2018.00908
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Tele-Video-Consultation for the Neuro-Surgical Emergency Management at the General Hospitals in Italy

Abstract: Background: Neuro-surgical emergencies are serious (long-term disability and high mortality) and costly to the national health services. Tele-medicine intervention can facilitate to reduce this gap. Our study aims to evaluate the cost-effectiveness of tele-video-consultation intervention for the management of neuro-surgical emergencies in the general hospitals.Methods: We retrieved health service data from the tele-consultation service, online tele-medicine database portal and hospital patient registry, betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…Although some extant literature has suggested that tele-neurology is not more cost-effective compared to conventional neurology service, especially with teleconsultation ( 54 , 55 ), its long-time cost-effectiveness has now been established ( 56 , 57 ). In most SSA countries, where a significant proportion of the population are not covered by health insurance, new tele-neurology services will need to demonstrate that people can get quality telehealth and tele-neurology services at cost-effective rates.…”
Section: Aces Strategic Focusmentioning
confidence: 99%
“…Although some extant literature has suggested that tele-neurology is not more cost-effective compared to conventional neurology service, especially with teleconsultation ( 54 , 55 ), its long-time cost-effectiveness has now been established ( 56 , 57 ). In most SSA countries, where a significant proportion of the population are not covered by health insurance, new tele-neurology services will need to demonstrate that people can get quality telehealth and tele-neurology services at cost-effective rates.…”
Section: Aces Strategic Focusmentioning
confidence: 99%
“…face to face). ; paediatric 18-28,30-37,49,51,57,58,77,82,85,87,95-99 ; mixed 54,61,64,82,92 ; unknown 70,80 ; traumatic brain injury 18-37,41,43,47-51,55-60,64,66,68,69,77-79,82-84, 87,90,91,93,95-99 ; spinal cord injury 38,39,42,[44][45][46]62,63,65,71,81,88,89,94 ; multi-trauma [52][53][54]61,67,80,85,86,92 ; orthopaedic 40 ; burns 70 ; therapy 18-28,30-39,42- ; assessment 29,39,41,[52][53][54]61,64,67,68,80,81,85,86,88,92 ; education 82 ; specialist consult…”
Section: Health-related Outcomesmentioning
confidence: 99%
“…For some, feasibility was established by the number of completed telehealth sessions. 33,45,[51][52][53][54][55][56][57] The literature cites several reasons as to why sessions could have been well attended, which include 'ease of use' as reported by participants, 30,36,57,58 the accessibility of the telehealth intervention, 59,60 the convenience, 40,[60][61][62] and timeliness, 61,63,64 which then reduced the impact of appointments on patients' daily lives.…”
Section: Health-related Outcomesmentioning
confidence: 99%
“…Выполнена в одной части публикаций речь идет именно о доступности помощи и соответственно ее большей эффективности, другая часть убедительно доказывает снижение стоимости лечения конкретного пациента при неизменном качестве лечения [19,21]. Предпосылками развития и актуализации этого направления в нашем случае может являться большая территория страны и низкая плотность населения в отдельных ее регионах, а также существующие различия в финансировании региональных систем здравоохранения на душу населения, местами низкая доступность специализированной и высокотехнологичной медицинской помощи [16,22].…”
Section: клинический примерunclassified
“…В литературе можно встретить много публикаций об использовании телемедицины или телекоммуникативных технологий в различных отраслях медицины: неврологии, нейрохирургии, психиатрии, онкологии, гинекологии. Основной целью использования телемедицины было снижение затрат на лечение и повышение эффективнос ти и доступности помощи [16,17,18,19,20,21]. При этом * http://www.americantelemed.org возможность непрерывного профессионального образования без отрыва от места работы.…”
Section: клинический примерunclassified